Gynecological Problems of Postmenopausal Women and Their Health Care-Seeking Behavior in Rural Community - Begum, Husneara; Rahim, Riffat (Journal of Enam Medical College, 2018)
Background: Gynecological problems and health care-seeking behavior of postmenopausal women vary among populations and societies. Few data are available about times and types of gynecological problems of postmenopausal women and health care-seeking behavior, socio-demographic and reproductive factors among rural women of Bangladesh. Objectives: The present study was conducted to find out the prevalence of gynecological problems, to identify socio-demographic factors and to identify the health care seeking-behavior of rural postmenopausal women. Materials and Methods: This cross-sectional study was conducted in women aged 50−70 years. A purposive sampling technique was used to retrieve data from 252 postmenopausal women from 3 villages of Savar Upazilla of Dhaka, Bangladesh. Results: The mean age of our study population was 57.27 ± 6.08 years, and the mean menopausal age was 48.20 ± 3.226 years. Regarding prevalence of gynecological problems, 28% had vaginal dryness, 5% had per vaginal bleeding, 9% had urinary problems, and 4% had something coming down per vagina. For primary treatment, 43% went to pharmacy, 29% went to private chamber or private clinic, and only 22% went to government hospitals for their general health problems. Some significant association was found between age of marriage, number of fertility and gynecological problems. Conclusion: Further studies are needed with a larger sample size to identify different life style, diet, and socio-cultural characteristics and to better understand the health care-seeking behavior of women of rural communities. J Enam Med Col 2018; 8(3): 135-138